(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
7 types of disasters of a technogenic nature are included in the emergency situations of a technogenic nature, which are specified in the Resolution of the Cabinet of Ministers of the Republic of Uzbekistan No. 455 dated October 27, 1998